Coupling external with internal exposure metrics of trihalomethanes in young females from Kuwait and Cyprus - Gängler, Stephanie; Makris, Konstantinos C.; Bouhamra, Walid; Dockery, Douglas W. (My University, 2018)
The Eastern Mediterranean and the Middle Eastern regions are both understudied in terms of possible environmental health risks for their populations. Water scarcity and desalination treatment provide the general population of countries from these regions (e.g., Kuwait and Cyprus) with unique tap water characteristics. This study investigated the association between external (tap water and 24 h personal air samples) and internal (urine) THM exposure metrics that reflected information about THM-related habits and activities collected using questionnaires and time activity diaries. The study population comprised of young females residing in either Kuwait (n = 13) or Cyprus (n = 22). First morning urine voids were collected on 2 consecutive days. Urinary creatinine-adjusted total THM (TTHM) levels were higher in Kuwait (median (interquartile range): 1044 (814, 1270) ng/g) than in Cyprus (691 (510, 919) ng/g, Po0.05). Median personal air TTHM levels in Kuwait (1.4 (0.7, 1.7) μg/m3) were higher than those in Cyprus (0.9 (0.5, 1.4) μg/m3), but did not reach statistical significance (P = 0.17). Median tap water TTHM in Kuwait (6.7 (5.4, 11.6) μg/l) did not correlate with urinary or air THM and they were lower than those in Cyprus (29.5 (20.1, 48.0) μg/l; Po0.01). Despite that tap water did not contain chloroform (TCM), TCM was detected in both air and urine samples in Kuwait, suggesting other TCM exposure sources, such as household cleaning activities. Total duration of activities and mopping were significantly correlated with air and urine THM in Kuwait, as reported in the time activity diary. Personal air and urine exposure metrics were correlated in Kuwait (TTHM ρ = 0.62, Po0.05), but not in Cyprus (TTHM ρ = − 0.32, P40.05). Time-activity diaries and urinary THM seemed to be useful measures of THM exposures in Kuwait. Coupling both external with internal exposure metrics could find use in population health studies towards further refining the association between environmental exposures and health outcomes.
Keywords: Biomonitoring; Brominated trihalomethanes; Disinfectant; Disinfection byproducts; Passive sampler